Gender as a moderating variable of e-payment / Khairul Azfar Adzahar ... [et al.] - Adzahar, Khairul Azfar; Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The age of technology and the current global pandemic of Coronavirus disease 2019 (COVID-19) has led to significant use of e-commerce and online payment gateways to pay for the purchase. Physical distancing policy and government encouragement for the public to adopt the e-payment method due to the increased number of active COVID-19 cases contribute to the increased importance of e-payment (Aji et al., 2020). Mobile phones have evolved into all-function gadgets since its first introduced widely back in the 90s. Traditionally, mobile phones provide a telephony function that enables people to communicate from widely removed points. However, the use of mobile phones has drastically changed since the introduction of the first mobile operating systems (OS) in the early 2000s. Today, people not only use their mobile phones just to have interactive communication between two points but also to make purchases online. Various efforts have been made by the relevant authorities and businesses to encourage the use of online payments as an alternative to cash payments by providing special offers, cash rebates, and others. However, there are still a few consumers who are less convinced in the use of online payments due to several security risk factors associated with the use of online payments such as data misuse, fraud, and scams. Previous studies mainly focused on assessing the extent to which security risks can influence a person to use or not use online payments. However, there is a lack of studies that assess the extent to which demographic factors influence the impact of online payment usage by consumers.